2022
DOI: 10.1177/1934578x221077820
|View full text |Cite
|
Sign up to set email alerts
|

Network Pharmacology-Based Strategy to Investigate the Anti-Breast Cancer Mechanisms of Spatholobus suberectus Dunn

Abstract: Spatholobus suberectus Dunn (SSD) possesses potential antitumor activity; however, the mechanism underlying its anti-proliferative effect on breast cancer is unclear. In this study, we explored potential SSD targets for breast cancer treatment through a network pharmacology approach. First, by integrating multiple databases, a total of 16 potential bioactive compounds and 252 targets were screened. Differentially expressed genes (DEGs) were screened by analyzing breast cancer gene chip data from The Cancer Gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 50 publications
(49 reference statements)
0
6
0
Order By: Relevance
“…Jiang's group designed a virtual screening to predict potential 5-LOX inhibitors from S suberectus stems by Autodock and comparative molecular field analysis. The study suggested that liquiritigenin (49), catechin (65), butin (53), and gallocatechin (64) were the most potential candidates for inhibiting 5-LOX activity. 41 Recent studies provided important evidence for the antiinflammatory effects of S suberectus stems, which is ethnopharmacologically relevant to traditional medicine.…”
Section: Antiinflammatory Activitiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Jiang's group designed a virtual screening to predict potential 5-LOX inhibitors from S suberectus stems by Autodock and comparative molecular field analysis. The study suggested that liquiritigenin (49), catechin (65), butin (53), and gallocatechin (64) were the most potential candidates for inhibiting 5-LOX activity. 41 Recent studies provided important evidence for the antiinflammatory effects of S suberectus stems, which is ethnopharmacologically relevant to traditional medicine.…”
Section: Antiinflammatory Activitiesmentioning
confidence: 99%
“…39 Another study focused on the effects of liquiritigenin ( 49), which is one of the major isoflavones from S suberectus, in atopic dermatitis. Liquiritigenin (49) was shown to block T-cell activation by reducing IL-2 production and CD69 expression via the NF-κB and MAPK pathways. In vivo experiments on dinitrochlorobenzene-exposed atopic dermatitis in mice also indicated the benefits of oral treatment with liquiritigenin (1 mg/mL, 5 times × 4 weeks), such as reduction of ear dermis and epidermis thickness, downregulation of IgE level, and recovery of tissue structure, when compared to the untreated group.…”
Section: Antiinflammatory Activitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on network pharmacology, Zeng et al [11] explored the molecular mechanism of salidroside sensitization by using doxorubicin in the treatment of cervical cancer. Our previous research using network pharmacological analysis also revealed that PPARγ is a potential therapeutic target of Spatholobus suberectus Dunn [12]. Thus, network pharmacology may be able to uncover the intricate mechanisms underlying the antiproliferative activities of MET due to its propensity to investigate the pharmacological mechanisms of natural products.…”
Section: Introductionmentioning
confidence: 99%